PERBEDAAN TINGKAT PROKASTINASI PADA MAHASISWA DITINJAU DARI METODOLOGI PEMBELAJARAN - Ananta, Aliffia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract Procrastination is a deliberate deliberate postponement and does other unnecessary work. Prokrastinya many experienced by students and influential on learning outcomes so it is important to be studied. This study aims to determine the level of student academic procrastination in terms of learning methods used by lecturers. Learning method in this research is Teacher Centered Learning (TCL) and Student CenteredLlearning (SCL). Subjects in this study as many as 150 students taken by purposive sampling, 75 subjects were students who got TCL method and 75 subjects were students who got SCL method. Data collection is done by using procrastination scale. Procrastination Scale consists of 16 items that have the validity of ≥ 0.03 with reliability of 0.805. The result of the research shows that there is no difference of academic procrastination between students who get TCL learning method with students who get SCL learning method.Key Words: Procrastination, Teacher Centered Learning, Student Centered Learning